2018
DOI: 10.21276/aanat.2018.4.2.8
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Student Perception of Virtual Dissection Table (Anatomage) at GSL Medical College, Rajahmundry

Abstract: Introduction:The Anatomage Table is the only fully segmented real human 3D anatomy system. Individual structures are reconstructed in accurate 3D and it helps the medical pre-clinical students to explore and understand human anatomy like never before and even beyond a cadaveric dissection. Anatomage is an interface that affords students the opportunity to explore life-size anatomy on an interactive 3D table. [1] Aim and Objective: The aim of the study was to gather student opinion regarding this virtual dissec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 3 publications
1
11
0
5
Order By: Relevance
“…However, the cons of using Anatomage are the variation in the human body (supernumerary muscles, variation in patterning of nerves and blood vessels) cannot be apparent onto the Anatomage table Moreover, the sense of touch of vessels, nerves and internal body structures cannot be gained, and the color of tissues is different from real ones. 11 , 12 The variation in the learning resources of the anatomy using cadaver dissection and 3D Anatomage help in developing deeper learning, which increases knowledge retention and its clinical relevance. 7 , 13 Therefore, 3D Anatomage was implemented in anatomy teaching in addition to cadaver dissection in the department of anatomy at UQUMED.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the cons of using Anatomage are the variation in the human body (supernumerary muscles, variation in patterning of nerves and blood vessels) cannot be apparent onto the Anatomage table Moreover, the sense of touch of vessels, nerves and internal body structures cannot be gained, and the color of tissues is different from real ones. 11 , 12 The variation in the learning resources of the anatomy using cadaver dissection and 3D Anatomage help in developing deeper learning, which increases knowledge retention and its clinical relevance. 7 , 13 Therefore, 3D Anatomage was implemented in anatomy teaching in addition to cadaver dissection in the department of anatomy at UQUMED.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with the findings of this study, it has been found that students understand the locations and relationships of different internal structures when utilizing Anatomage compared to the students using cadaver dissection. 12 , 21 , 22 Moreover, a high proportion of participating students benefitted from the integration of imaging in 3D Anatomage, since it enabled them to understand how anatomy envisioned through medical imaging prepared them for clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Donnelly et al ( 2009) report the Visible Human Dissector is extremely useful for understanding cross-sectional anatomy. There is clearly an advantage to having technology to teach gross anatomy (Anand & Singel, 2017;Bharati et al, 2018;Fyfe et al, 2018). For example, Bharati et al (2018) report that 90% of 150 students agreed that the Anatomage table should be used in conjunction with dissection rather than instead of it.…”
Section: Technologymentioning
confidence: 99%
“…Based on the literature student surveys show that the best approach to learning anatomy included CD in conjunction with new and alternative modalities (Dissabandara et al, 2015;Rehman et al, 2012;Romero-Reveron, 2017). For example, Bharati et al (2018) report that 90% of 150 students surveyed wanted the Anatomage table to be used in conjunction with CD.…”
Section: The Proposed Integration Approachmentioning
confidence: 99%
“…The Human Anatomy course is under a digital revolution enabled by virtual dissection. Several publications show that "Anatomage" table-based education has proven to be effective [28,29]. Virtual Dissection Table "Anatomage" (developed by a 3D medical technology company located in San José (California) in conjunction with Stanford University's Clinical Anatomy Division) is one of the most advanced visualization systems that is used as an instrument in anatomy education [30].…”
Section: Accessibility Of Digital Images and 3dp Models 221 Teaching/learning Environments With Digital Imagesmentioning
confidence: 99%